Fluorescent and magnetic nanoparticles for bacteria detection and separation - Phang, Sophia Xue Hui (2018)
The study of microarrays has become a major tool for wide spectrum of chemical and biomedical applications and was implemented in diverse fields extending from fundamental genomic study to clinical analysis. Currently, conventional static microarray hybridization methods have been employed, however this platform resulted to a slow turnaround time of 8 – 24 hours due to diffusion limited reaction kinetics. Various dynamic hybridization methods such as, micro-fluidic chaotic mixer and acoustic microflows, were established to overcome this fundamental challenge. Nevertheless, these designs were difficult to be implemented, as it required supplementary device which were not usually available in biological and clinical settings, additionally these platforms also complicated the microarray bioanalysis. In this report, magnetic nanochains fabricated were used to induce rapid mixing in microarray, and resulted to a high mixing efficiency of 80% within the first minute. In this experiment, the result also exhibited that self-mixing nanocatalysts placed in a spinning magnetic field resulted 60% increase in reaction kinetics than that of unstirred reaction. It took only 30 minutes for self-mixing nanocatalysts in DNA Microarray to achieve the same mixing results as static DNA microarray, which in turn, required 8 hours. This report proposed to utilize multifunctional magnetic nanochains based dynamic mixer to overcome diffusion barrier limitation in microarray assay. The rapid mixing has proved to reduce the localized target depletion resulting in rapid turnaround enhanced sensitivity. As a result, the efficiency of hybridization had significantly improved and the target DNA were uniformly delivered across. With the new knowledge obtained through this research study, new possibilities of biomolecules applications such as in medical diagnostics and the biocatalyst therapeutics have been offered for future biomedical advancements.